A study on the angular distortion in tee type full penetrated welded joint fabricated by the laser-arc hybrid welding*. Issue 12 (2nd December 2017) - Tsumura, Shuichi; Murakami, Koji; Gotoh, Koji
Abstract: The reducing effect of the angular distortion in T-type full penetrated welded joints fabricated by laser-arc hybrid welding was investigated. The angular distortion caused by the laser-arc hybrid welding were measured and compared with one caused by CO2 gas shielded-arc welding. As a result, the amount of angular distortion by laser-arc hybrid welding was the same level as one in the case of forming a leg size of F1 grade regulated by the Common Structural Rules for Bulk Carriers by applying arc welding. In addition, numerical analysis of the welding deformation was carried out by thermal elastic–plastic finite element analysis and these results were generally consistent with the measured results. Moreover, the effect on the FE result of the penetrated shape is discussed.